2010
DOI: 10.1007/s10995-010-0658-8
|View full text |Cite
|
Sign up to set email alerts
|

Consultative Care Coordination Through the Medical Home for CSHCN: A Randomized Controlled Trial

Abstract: The purpose of this study was to examine the impact of a care coordination intervention aimed at improving the medical home for children with special health care needs (CSHCN). 100 CSHCN referred by a Medicaid managed care plan were randomly assigned to a care coordination intervention or to a wait list comparison group that received standard care. For the intervention group, a care coordinator supported the medical home by consulting with primary care providers at multiple practices to develop an integrated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 18 publications
1
83
1
Order By: Relevance
“…Our results support study findings of a positive impact on patient experience among children with special health care needs who were part of a PCMH 14,15 and other child patient samples. 16 Together, these findings suggest that the PCMH model may hold promise for improving patient experience even if there is still a question of whether there are improvements in quality or cost over the short term.…”
Section: Discussionsupporting
confidence: 87%
“…Our results support study findings of a positive impact on patient experience among children with special health care needs who were part of a PCMH 14,15 and other child patient samples. 16 Together, these findings suggest that the PCMH model may hold promise for improving patient experience even if there is still a question of whether there are improvements in quality or cost over the short term.…”
Section: Discussionsupporting
confidence: 87%
“…14,39 Our study aligns with national efforts to implement medical homes to reduce unmet specialty care. However, our findings suggest the implementation of care coordination is an effective means to decrease family-perceived unmet need as an interim step on the journey to comprehensive medical home transformation.…”
Section: Discussionmentioning
confidence: 57%
“…31 A 2011 study in children and youth with special health care needs and their families who received care coordination and individualized care plans via a Medicaid managed care plan study reported improved satisfaction with mental health services and specialized therapies and participants were observed to have a decline in unmet needs, improved satisfaction with specialty care, and improved ratings of child health and family functioning. 32 In a busy medical practice, care coordination fosters improved productivity and efficiency by transferring the mechanics of follow-up care, referrals, equipment acquisition, letters of medical necessity, patient information, transition of care, and previous authorization to care coordinators rather than physicians. As such, efficiency ensues because physicians can spend less time on nonclinical issues for patients.…”
Section: Benefits Of and Evidence For Care Coordinationmentioning
confidence: 99%